2019
DOI: 10.1088/1361-6560/ab49ea
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lung tumor motion using nonlinear autoregressive model with exogenous input

Abstract: The present note addresses the development of a lung tumor position predictor to be used in dynamic tumor tracking radiotherapy, abbreviated as DTT-RT. As there exists 50–500 ms positioning lag in the control of the multi-leaf collimator (MLC) of commercial medical linear accelerators, prediction of future lung tumor position with sufficiently long prediction horizon is inevitable for the successful implementation of DTT-RT. The present article proposes a lung tumor position predictor, which is classified as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Module#2 solves the regression problem of estimating the 3D movement amount from the 2D MRI pixel values and, at the same time, constructs a network by LSTM to eliminate the deviation of the irradiation position due to the imaging time of cine-MRI and the device delay [ 11 , 12 ]. This made it possible to predict the respiratory cycle from the movement before and after the frame of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Module#2 solves the regression problem of estimating the 3D movement amount from the 2D MRI pixel values and, at the same time, constructs a network by LSTM to eliminate the deviation of the irradiation position due to the imaging time of cine-MRI and the device delay [ 11 , 12 ]. This made it possible to predict the respiratory cycle from the movement before and after the frame of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have used ML algorithms for predicting tumour motion based on past motion, 72–89 including in MRI‐guided radiotherapy 90–92 and ultrasound‐guided radiotherapy 93 . A comparison study of ML algorithms was made by Sharp et al.…”
Section: Prediction Of Tumour Motionmentioning
confidence: 99%
“…Several studies have used ML algorithms for predicting tumour motion based on past motion, [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] including in MRI-guided radiotherapy [90][91][92] and ultrasound-guided radiotherapy. 93 A comparison study of ML algorithms was made by Sharp et al and showed that most ML algorithms have a lower localisation error compared to no prediction.…”
Section: Prediction Of Tumour Motionmentioning
confidence: 99%
“…Motion prediction frameworks have been implemented to address these combined latency issues when monitoring breathing motion by predicting near-future motion to guide gating or machine adjustments (Shirato et al 2000, McCall andJeraj 2007). Breathing motion prediction methods have been extensively studied, and several methods have been explored to address this problem, including linearized regression model, nonlinear estimation model, Kalman filtering and artificial neural networks (Isaksson et al 2005, Ruan and Keall 2010, Sun et al 2017, Jiang et al 2019, Li et al 2020.…”
Section: Introductionmentioning
confidence: 99%